Pemanfaatan Limbah Mat dengan Penambahan Ekstrak Biji Pala (Myristicafragans) Terhadap Kematian Nyamuk Aedes sp - Andriyani Setyaningrum; Yamtana Yamtana; Sarjito Eko Windarso (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Aedes sp is the transmitting vector for Dengue Haemorrhagic Fever (DHF). One of the mosquitocontrolling measure is by using insecticides with electric mat. One of bological insecticides whichcan be used is nutmeg or Myristicafragans. The extract of the kernels contains tanine and saponine. The purpose of this study was to determine the effect of concentration variation of nutmegkernel extract as additional substance for used electric mat against the mortality of Aedes sp.The study was a quasi experiment with post test only control group design. The collected datawere analysed by using one way anova at 95 % significance level, to determine the effect of theconcentration variation (15 %, 20 %, and 25 %) on the death of Aedes sp. LSD test was thenperformed to determine the most effective concentration. The results showed that the three concentrations of nutmeg extract influence the death of Aedes sp (p-value < 0,001), and the mosteffective concentration was 25 % with 95 % mosquito mortality.